2019
DOI: 10.5539/ies.v12n9p76
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Peer Feedback in Developing Students’ English Writing Ability in L2 Writing Class

Abstract: The study aimed at investigating the effects of peer feedback on students' English writing ability in L2 writing class. A mixed-methods research, an embedded experimental design was employed, making use of a writing pretest and post-test and self-written reflection in the experiment. Data were quantitatively analyzed through a dependent simple t-test, and content was thematically analyzed for qualitative data. The participants were 21 undergraduate students majoring in English in the three southernmost border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
2
19
0
2
Order By: Relevance
“…The results are in line with the views of the supporters who highlighted the effectiveness of the students' interactions in developing their writing skills (e.g. Elola & Oskoz, 2010;Kuyyogsuy, 2019;Mazdayasna & Zaini, 2015;Neumann & McDonough, 2014a;Nikoopour & Aminifarsani, 2010;Wiggleworth & Storch, 2009). Additionally, results of the study concerning the second research question revealed that unstructured collaborative pre-writing tasks improved Iranian EFL learners' essay writing skills.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The results are in line with the views of the supporters who highlighted the effectiveness of the students' interactions in developing their writing skills (e.g. Elola & Oskoz, 2010;Kuyyogsuy, 2019;Mazdayasna & Zaini, 2015;Neumann & McDonough, 2014a;Nikoopour & Aminifarsani, 2010;Wiggleworth & Storch, 2009). Additionally, results of the study concerning the second research question revealed that unstructured collaborative pre-writing tasks improved Iranian EFL learners' essay writing skills.…”
Section: Resultssupporting
confidence: 83%
“…Purely collaborative tasks which have been merely done by students has been named structured collaborative tasks which involved merely students-students' interaction (e.g. Ameri-Golestan & Dousti, 2015;Elola & Oskoz, 2010;Kuyyogsuy, 2019;Mazdayasna & Zaini, 2015;Mercer & Littleton, 2007;Neumann & McDonough, 2014a;Nikoopour & Aminifarsani, 2010;Rashtchi & Beiki, 2015;Storch, 2005;Wiggleworth & Storch, 2009). Students-students' interaction (structured collaborative tasks) is in line with inter subjectivity theory.…”
Section: Introductionmentioning
confidence: 83%
“…A motivated language learner forms a deeper personal connection to what they learn and how they learn which positively influence on metacognition and learner autonomy (Liu, 2015;Soberg, 2018). It is therefore recommended that a strong language education system in Bangladesh is ensured to safeguard the responsibility of the teachers (Kaur, 2014;Nguyen & Walkinshaw, 2018), reformation of the course curricula and assessment system based on learning needs (Chowdhury & Haider, 2012;Emler et al, 2019;Kirkpatrick & Zang, 2011), provision of necessary environment and infrastructure (Cohen & Bhatt, 2012;Lodhi et al, 2019), and encourage the roles of students and their peers (Kaur, 2017;Kuyyogsuy, 2019;Mak & Wong, 2017) to develop learners' motivation and foster their autonomous learning opportunities.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…There are recent studies revealing the strengths of PF in developing EFL/ESL writing skills (Austria, 2017;Brusa & Harutyunyan, 2019;Khalil, 2018;Min, 2016). Kuyyogsuy (2019) investigated the influence of PF on students' writing ability. The findings showed that the students' writings had improved significantly.…”
Section: Literature Reviewmentioning
confidence: 99%